The impact of literature through short stories on English language instruction - Juentri Enfira; Kasmaini Kasmaini (Pusat Studi Bahasa dan Publikasi Ilmiah, 2026)
This study investigates the effectiveness of integrating literature, specifically short stories, into English language instruction for junior high school students. Conducted at SMPIT AN-NIDA' Lubuklinggau, it aims to determine if short stories enhance vocabulary acquisition, reading comprehension, and overall language proficiency compared to traditional methods. The research addresses the need for engaging, culturally relevant teaching strategies in Indonesian Islamic schools. A quasi-experimental design was employed with a population of 60 students divided into two classes (30 students each). Class A (experimental group) received English instruction incorporating short stories (e.g., adapted narratives with themes of morality and adventure), while Class B (control group) followed conventional grammar-focused lessons. Pre- and post-tests measured English proficiency (vocabulary, comprehension, and grammar scores out of 100). Data were analyzed using descriptive statistics (means) and an independent samples t-test to assess differences between groups (α = 0.05). Pre-test means showed similar baseline proficiency: Class A (M = 65.2, SD = 8.1) and Class B (M = 66.8, SD = 7.9). Post-test means indicated improvement in both groups, but Class A outperformed Class B: Class A (M = 78.5, SD = 6.5) vs. Class B (M = 71.2, SD = 7.2). The independent t-test revealed a significant difference (t (58) = 4.23, p = 0.001), confirming that the use of short stories has a real positive impact on improving students’ English language skills.